Impact of Bagasse Carbonization Temperature on Activated Carbon Properties for Chromium Hexavalent Adsorption and an Environmental Analysis - Maulida Zumrotul Azizah; Nur Rochmah Septia Amanda; Dian Rahmawati; A.S. Dwi Saptati Nur Hidayati (Jurnal Bahan Alam Terbarukan, 2025)
The electroplating industry releases a high concentration of Chromium Hexavalent [Cr(VI)] up to 48.7 mg/L, significantly surpassing the quality standard of 0.1 mg/L. The activated carbon adsorption process is a cost-effective and straightforward approch to reducing the concentration of Cr(VI). Activated carbon can be produced from bagasse which is rich in cellulose. Due to limited information on the effect of carbonization temperature on the properties of activated carbon from bagasse, this study aims to identify the effect of carbonization temperature range from 450°C to 600°C and how it affects the performance of adsorbing Cr(VI). In addition, this study analyses the environmental impact of activated carbon production from bagasse with different temperature operating conditions through life cycle assessment. The research has four stages: carbonization, activation, adsorption, and environmental impact analysis. The result indicates that higher temperatures enhance the performance of activated carbon to adsorb Cr(VI) and produce the best-activated carbon quality. However, the environmental impact of performing at the highest temperature (600°C) is also the highest while having the lowest yield. Therefore, a temperature of 550°C is suggested to achieve fair product quality with good adsorbing performance, high yield, and less harming the environment. The hotspots of the production process lie in the freshwater aquatic ecotoxicity, acidification, and human toxicity due to using of H2SO4 and electricity.